Quality Management of Principal Academic Supervision for Enhancing Teacher Pedagogical Competence: A Comparative Case Study of Two Indonesian Elementary Schools - Muthi Fadhilah; Eva Dianawati Wasliman (Papanda Publisher, 2026)
Teacher pedagogical competence remains critical for educational quality, yet many teachers struggle with planning, implementing, and evaluating instruction effectively. Academic supervision represents a vital quality management mechanism, though limited research examines how principals systematically integrate quality management principles into supervision practices. This study investigated quality management approaches to principal academic supervision in enhancing teacher pedagogical competence through comparative analysis of two elementary schools. A qualitative multiple case study design was employed at SDN 164 Karangpawulang and SDN 033 Asmi Bandung. Data were collected through semi-structured interviews with 12 participants (principals, vice principals, teachers), classroom observations, and document analysis. Thematic analysis following Braun and Clarke's framework was conducted to identify patterns across planning, implementation, evaluation, and follow-up stages. Both schools successfully implemented systematic supervision cycles aligned with quality management principles, though employing distinct approaches. SDN 164 emphasized standardized instruments from the Merdeka Mengajar Platform and Employee Performance Target integration, while SDN 033 excelled in collaborative supervision incorporating lesson study principles and reflective practices. Teachers demonstrated significant improvements in pedagogical competencies, translating into enhanced student engagement and learning outcomes. Effective supervision quality management requires balancing standardization with contextualization, evaluation with professional growth. The study advances theoretical integration of instructional leadership, quality management, and collaborative learning frameworks while offering actionable strategies for practitioners.